P3_11 Spartan Rocket Jump - Houghton, Kate; Clark, Ashley; Simms, Henry; Kuzemczak, Jacek (Physics Special Topics, 2012)
Â  This paper aims to find the height reached when a rocket propelled grenade is fired vertically downward by Master Chief, from the game Halo, whilst he is at the peak of his jump. In order to do this the conservation of momentum and energy from the explosion are considered. The height of the rocket powered jump was calculated to be 93.8m.